2018
DOI: 10.28955/alinterizbd.360031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in Terms of the Herbage Yield and Quality of Some Cereal Species Grown at Different Sowing Times

Abstract: Bu çalışma, Bingöl ekolojik koşullarında kışlık olarak yetiştirilen bazı buğday, arpa ve tritikale çeşitlerinde farklı ekim zamanlarının ot verimi ve kalitesine olan etkisinin belirlenmesi amacıyla 2015-2016 yetiştirme sezonunda yürütülmüştür. Çalışmada bitki materyali olarak 1 adet tritikale (Ümranhanım), 1 adet iki sıralı arpa (Şahin 91), 1 adet altı sıralı arpa (Altıkat), 1 adet ekmeklik buğday (Pehlivan) ve 1 adet makarnalık buğday (Fırat-93) çeşidi kullanılmıştır. Araştırma Tesadüf Blokları Deneme Desenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Therefore, higher green forage and dry matter yield in the early planting may be attributed to the higher number of days between the first sowing time and the harvest compared to the other sowing times. Results on high forage yield in early planting are in accordance with the findings reported by CACAN and KARABULUT (2018); COSKUN and CACAN (2019), who carried out studies with different species and varieties in similar ecologies.…”
Section: Green Forage and Dry Matter Yieldssupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, higher green forage and dry matter yield in the early planting may be attributed to the higher number of days between the first sowing time and the harvest compared to the other sowing times. Results on high forage yield in early planting are in accordance with the findings reported by CACAN and KARABULUT (2018); COSKUN and CACAN (2019), who carried out studies with different species and varieties in similar ecologies.…”
Section: Green Forage and Dry Matter Yieldssupporting
confidence: 90%
“…Similarly, TEMEL and TAN (2002) stated that the plant height was shortened in late sowing. CACAN and KARABULUT (2018) reported that plant height of triticale varied between 76.0 and 82.8 cm in different sowing times. CACAN and KOKTEN (2017) who determined the appropriate sowing times of vetch varieties, reported that the plant height of Gorkem and Kralkızı vetch varieties was between 18.9 and 22.7 cm, and 15.2 and 19.6 cm, respectively.…”
Section: Plant Heightmentioning
confidence: 99%
See 3 more Smart Citations